On Decidability of the Theory Th(u, 0,1,<, +, f0,..., fn) - A. S. Snyatkov (Моделирование и анализ информационных систем, 2010)
In the paper we consider theories which are obtained from the Semenov arithmetics introducing functions fi,i > 0. They are called "hyperfuncctions" and they are obtained when we iterate an addition-connexctexd function. We have provexl, that such theories are model complete. It is also shown, that these theories are dexidable when the condition of eSexctive periodicity is satis&exd for hyperfuncctions.